Time Spent in Sedentary Activity Is Related to Gross Motor Ability During the Second Year of Life. Issue 5 (October 2019) - Hauck, Janet L.; Felzer-Kim, Isabella T.
Sedentary activity occupies a substantial amount of time during early childhood, with these habits influenced by changing trends in screen time for very young children. Among school-aged children, motor ability is inversely related to sedentary activity. However, the concept of sedentary activity is rarely investigated in toddlers, and thus little is known concerning its relationship with motor development during this rapidly changing and early period of life. Among two groups of toddlers, aged 18 months ( N  = 26) and aged 24 months ( N  = 16), this study investigated cross-sectional correlations of motor development (Bayley Scales of Infant Development—III) with daily sedentary activity (accelerometers). In both groups, gross motor ability, but not fine motor ability, was inversely correlated with time spent in sedentary activity. At 18 months, gross motor raw scores inversely correlated significantly with time in sedentary activity ( r  = −.533, p  < .001) but fine motor raw scores did not ( r  = .182, p  = .441). Also, at 24 months, gross motor raw scores inversely correlated with time in sedentary activity ( r  = −.563, p  = .029), while fine motor raw scores did not ( r  = −.112, p  = .425). These findings add important missing knowledge to the empirical literature regarding sedentary activity in toddlers and its relationship to emerging motor development. Future work might investigate best practices for measuring sedentary activity in this age-group and mechanisms behind its relationship with gross motor skills.